(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Warp-knitted mesh spacer fabrics are widely used as seat mattress for their excellent pressure-relief performance and heat and moisture comfortability; however, action and reaction between human body and spacer fabrics are still not well-known, which is attributed to the unknown contacting geometry. The main content dealt with in the paper is to measure surface geometry of warp-knitted mesh spacer fabric under spherical compression, and also to discuss the influence of sphere with different diameters on compression behaviour. Resin curing method was utilized to fix the surface geometry of compressed warp-knitted mesh spacer fabric, so as to obtain surface geometry functions of spacer fabrics. Experimental results demonstrate that the cross-sectional curves of both the non-contacting part and contacting part are exponential function and circular function, respectively. Moreover, correlations of maximum compressional strain between spherical compressions from different spheres were calculated, which reveals that there exist a good correlation between maximum compressional strain decrease and increasing diameter of sphere. The paper is helpful for studying compression behavior of warp-knitted mesh spacer fabrics and its interaction with different parts of the body in mattress materials.